Design of an Impulse-Debriefing-Spiral for Simulation Game Facilitation. (June 2021) - Schwägele, Sebastian; Zürn, Birgit; Lukosch, Heide K.; Freese, Maria
Background: Simulation gaming sessions can be understood as a sequence of briefing, game play, anddebriefing - with feedback loops and iterative steps in between. Often, these sessions are supported by a facilitator, who organizes the session, sets learning goals, and guides the players through briefing, game play anddebriefing (Taylor, Backlund & Niklasson, 2012 ), which we callfacilitation .Debriefing is a vital part of thefacilitation process, as according toCrookall (2010) andKriz (2010), it facilitates learning. Contrary to many traditional models that locate thedebriefing phase at the very end of a simulation gaming session, we conceptualize debriefing as reflection moments during the whole session, in which participants have the opportunity to reflect on their game play, experiences, and learnings.Facilitation is the process of enabling participants to address challenging situations of the game play, and make connections between the game play and the real environment the game refers to throughout the simulation gaming session. Method & Results: We analysed existingdebriefing literature within the Simulation & Gaming journal. This review revealed that many existing approaches do not sufficiently consider changing needs of participants during a simulation gaming session to allow for a direct reflection on what is happening. Instead, a large number ofdebriefing approaches focus on a post-action reflection only. Moreover, the approaches analysed in our article often are abstract and only provide scarce practical recommendations. In addition to the literature review, we draw conclusions from observations of our own work in and with simulation gaming sessions. Based on the related and our own work, we propose a new model for simulation gamefacilitation, which better connects moments of reflection with the game play - the Impulse-Debriefing-Spiral. Conclusions: We provide a holistic understanding ofdebriefing that helpsfacilitators when implementingsimulation games for learning purposes. Our model, called the Impulse-Debriefing-Spiral, conceptualizes the role offacilitation between briefing anddebriefing throughout the whole process of a simulation gaming session - starting with its planning to reacting on emerging needs of the participants in between, up to closing the session as last step before transferring new knowledge and competencies into a new context (learning transfer).